Industrial training report: Bahagian Hal Ehwal Akademik UiTM Machang / Muhammad Rosmaizul Maidin - Maidin, Muhammad Rosmaizul (Perpustakaan Tengku Anis, 2017)
The industrial training duration based on the period from 1st of August to 31st of December 2017 in Academic Affairs Division (Bahagian Hal Ehwal Akademik) UiTM Machang, Kelantan. The training consumes 5 months and not more than 6 days of absent. During the industrial training lots of activities being done and lots of new thing being learnt. Many things learned during industrial training are about management and workflow charts in this part of academic affairs. This is because, this part of the academic affairs is a place where there are a lot of management, especially academic management between students and lecturers. In addition, academic affairs also play a role in managing matters related to the learning, research and academic process for all academic programs in UiTM Kelantan. Academic affairs are also responsible for providing any hardware, needs or any kind of facilities for the learning and teaching process. To design or create an ATP system to the academic affairs unit, many of the processes needed to do include collecting all the information needed to prepare the system. After all the information and data from the previous system has been collected an analytical process will be made to facilitate system design of the system flow chart. The academic affairs section also really focuses on the development of systems for the organization and also uses external sources for system development.